Two-year retrospective cohort results on use of a dynamic unilateral brace for treatment of clubfoot: Can compliance and prevention of recurrence both be achieved?. (25th June 2022) - Farrar, Emily J; Lo, Michelle; Groothoff, Luke; Cunningham, Jerald; Theuri, Joseph
Objectives: The Ponseti method has led to vast improvements in outcomes for infants born with clubfoot deformity, but challenges with compliance during the bracing phase of the protocol remain. Unilateral braces promise higher compliance but often have led to unacceptably high recurrence. Methods: We have developed a novel unilateral brace for clubfoot deformity that strategically applies patient-specific, anatomically-targeted forces to the lower limb to maintain correction. We retrospectively reviewed the cases of 26 patients with minimum follow-up of 24 months. The data were analyzed for recurrence rates, caregiver-reported compliance, and differences in Pirani score, dorsiflexion, abduction, hindfoot eversion, and resting rotation between initial and final follow-up. Results: Most patients ( N = 23, 88%) were compliant with the bracing protocol. Two patients showed recurrence of deformity (8%). There were statistically significant improvements in Pirani score, dorsiflexion, abduction, hindfoot eversion, and resting external rotation. A subset of patients with sub-optimal correction at baseline showed improvement in all parameters across the course of bracing. Conclusions: This novel unilateral brace for maintenance of clubfoot correction after Ponseti treatment demonstrates rates of recurrence rates and caregiver-reported compliance at 2 years of follow up that are comparable to outcomes with traditional bilateral foot abduction orthoses.